Hepatic vasculitis presenting with multiple sterile liver abscesses in a patient with systemic lupus erythematosus - Wangkaew S. (2014)
Although biochemical evidence of liver disease is common in patients with systemic lupus erythematosus (SLE), clinical liver disease is uncommon. We report on a 26-year-old woman who presented with acute febrile illness, right upper abdominal pain and multiple hypo-dense lesions in the liver in a computed tomographic study that mimicked multiple liver abscesses. Multiple necrotizing hepatic granulomas and old occlusive hepatic arteritis were observed in the surgical liver specimen. She was later found to have SLE. This patient represented a rare case of SLE that had hepatic vasculitis with hepatic infarction mimicking multiple liver abscesses as an initial manifestation. © 2007 Asia Pacific League of Associations for Rheumatology and Blackwell Publishing Asia Pty Ltd.